2016
DOI: 10.15740/has/ijas/12.2/238-240
|View full text |Cite
|
Sign up to set email alerts
|

Weed management in cowpea [Vigna unguiculata (L.) Wasp.] under rainfed conditions

Abstract: :A field experiments was conducted for two consecutive Kharif seasons of 2012 and 2013 at Rajasthan Agricultural Research Institute, Durgapura, Jaipur to study the effect of weed management practices on cowpea under rainfed conditions. Results revealed that application of imazethapyr + imazemox @ 40 g ai/ha at 20 days after sowing (DAS) recorded lowest dry weight of both monocot and dicot weeds with highest weed control efficiency (84.8%). However, maximum seed yield (9.04 q/ha), net returns (Rs. 24718/ ha) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…In different weed management treatments it was found that treatments T 10 (2 HW + 2 IC Madukwe et al, (2012) and Gupta et al, (2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In different weed management treatments it was found that treatments T 10 (2 HW + 2 IC Madukwe et al, (2012) and Gupta et al, (2016).…”
Section: Resultsmentioning
confidence: 99%
“…The critical period of crop weed competition in cowpea has been identified as 20-30 days after sowing and presence of weeds beyond this period causes severe reduction in yields Gupta et al, (2016). Hence, weed control needs to be undertaken during initial period of crop growth.…”
Section: Issn: 2319-7706 Volume 6 Number 3 (2017) Pp 97-101mentioning
confidence: 99%
“…Studies have been conducted to evaluate weed management practices including IWM with the best agronomic yield in cowpea (Osipitan et al, 2013(Osipitan et al, , 2016Adigun et al, 2014), however, reports have shown that a management practice with best agronomic yield may not necessarily translate to best economic benefit to farmers (Gupta et al, 2016;Sepat et al, 2017). Therefore, the objectives of this study were to evaluate: (1) economic benefits of weed management methods used singly and in an integrated approach; (2) influence of row-spacing on economic benefits of weed management methods.…”
Section: Introductionmentioning
confidence: 99%
“…Yield losses cause by weeds alone in cowpea production can range from 25% to 76% depending on the cultivar and environment (Adigun et al, 2014;Gupta et al, 2016;Osipitan et al, 2016;Ugbe et al, 2016). Problems caused by weed in cowpea production include reduction in crop yield, less efficient land use, higher cost of production due to insects and plant disease control, reduction in crop quality, water management problems, and less efficient utilization of labour (Patil et al, 2014;Gatachew et al, 2015;Prabhu et al, 2015;Singh et al, 2016).…”
Section: Weed Problem In Cowpeamentioning
confidence: 99%
“…A season long weed interference could potentially reduce cowpea yield by 53 to 76% (Olorunmaiye & Ogunfolaji, 2002;Adigun et al, 2014;Gupta et al, 2016). Allowing weed to interfere with cowpea growth for up to 50 days after crop emergence (DAE) reduced cowpea yield by 26 to 75% (Olorunmaiye & Ogunfolaji, 2002;Adigun et al, 2014).…”
Section: Impact Of Weed Interference Duration and Critical Time Of Wementioning
confidence: 99%